Elements of tourism policy in developing countries: report by the secratariat of UNCTAD - United Nations Conference on Trade and Development (New York, United Nations, 1973)
The subjects covered in this work include: the past and prospective growth of international tourism; tourism and national economy; policies and institutions of tourism; tourism resources and their utilization; the supply of accommodation; and infrastructure for tourism
"United Nations publication. Sales no. E.73.H.D.3."
Includes bibliographical references.
osc 29/01/2019
Loans
Keywords: Tourism